2020
DOI: 10.3892/etm.2020.9198
|View full text |Cite
|
Sign up to set email alerts
|

CGA ameliorates cognitive decline by regulating the PI3K/AKT signaling pathway and neurotransmitter systems in rats with multi-infarct dementia

Abstract: Multi infarct dementia (MID) is a form of dementia that is preventable and treatable. However, at present, the drugs used in MID treatment were developed for Alzheimer's disease. While only a limited range of drugs is available, the incidence of MID is increasing year on year. The present study aimed to investigate the effect and underlying mechanisms of a combination of ginsenosides and astragalosides (CGA) on cognitive decline in rats with MID. A rat model of MID was established using micro-thromboembolism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Studies have demonstrated that the MAPK signaling pathway is associated with lipid (Wang et al, 2018;Zhang et al, 2018) and energy metabolism (Zheng et al, 2016;Kim et al, 2018) that regulates glucose metabolism (Long et al, 2015). Moreover, studies have also shown that PI3K-Akt signaling is involved in glucose (Ruzzi et al, 2020), lipid (Fu et al, 2020), and energy metabolism [79,80]. Based on the present results of the enrichment analysis, it appears that the identified DEGs may regulate feed efficiency through signaling pathways related to energy metabolism and substance metabolism.…”
Section: Discussionmentioning
confidence: 67%
“…Studies have demonstrated that the MAPK signaling pathway is associated with lipid (Wang et al, 2018;Zhang et al, 2018) and energy metabolism (Zheng et al, 2016;Kim et al, 2018) that regulates glucose metabolism (Long et al, 2015). Moreover, studies have also shown that PI3K-Akt signaling is involved in glucose (Ruzzi et al, 2020), lipid (Fu et al, 2020), and energy metabolism [79,80]. Based on the present results of the enrichment analysis, it appears that the identified DEGs may regulate feed efficiency through signaling pathways related to energy metabolism and substance metabolism.…”
Section: Discussionmentioning
confidence: 67%
“…In addition to the effects of breviscapine on apoptosis, inflammation, and oxidative stress, we observed its influence on PI3K/Akt and NF-κB pathways. A combination of ginsenosides and astragalosides was verified to improve cognitive impairment in rats with multi-infarct dementia through regulation of PI3K/Akt pathway (Fu et al, 2020).…”
Section: Breviscapine Promoted Pi3k/akt Pathway and Inhibited Nf-κb P...mentioning
confidence: 98%
“…TCM also reduces neuronal apoptosis and loss of neurons caused by excessive autophagy ( 34 , 35 ). Beyond that, TCM can improve the pathways related to memory storage, and relieve the symptoms of memory loss by protecting the normal energy metabolism of the brain, restoring the structure and function of synapses and restoring neurotransmitter related neurotransmission ( 36 , 37 ).…”
Section: Introductionmentioning
confidence: 99%